A 400 Gbps/100 m free-space optical link. (9th January 2017) - Lin, Chun-Yu; Lu, Hai-Han; Ho, Chun-Ming; Cheng, Ming-Te; Huang, Sheng-Jhe; Wang, Yun-Chieh; Chi, Jing-Kai
Abstract: A 400 Gbps/100 m free-space optical (FSO) link with dense-wavelength-division-multiplexing (DWDM)/space-division-multiplexing (SDM) techniques and a doublet lens scheme is proposed. To the best of our knowledge, this is the first time that a link adopting DWDM and SDM techniques and a doublet lens scheme has demonstrated a 400 Gbps/100 m FSO link. The experimental results show that the free-space transmission rate is significantly enhanced by the DWDM and SDM techniques, and the free-space transmission distance is greatly increased by the doublet lens scheme. A 16-channel FSO link with a total transmission rate of 400 Gbps (25 Gbps/ λ × 16 λ = 400 Gbps) over a 100 m free-space link is successfully demonstrated. Such a 400 Gbps/100 m DWDM/SDM FSO link provides the advantages of optical wireless communications for high transmission rates and long transmission distances, which is very useful for high-speed and long-haul light-based WiFi (LiFi) applications.